Efektifitas Peraturan Daerah Kota Tanjungpinang Nomor 7 Tahun 2010 tentang Bangunan Gedung terkait Penerbitan Izin Mendirikan Bangunan Rumah Tinggal di Kota Tanjungpinang - Agus Haryono (Journal of Law and Policy Transformation, 2019)
Residential Building is a part of the basic need for humans to carry out their activities. The developments in each region are rapidly growing. The problems that arise from construction activities are when they are not in accordance with their functions and spatial plans. Accordingly, the Tanjungpinang city government issued a regulation of the Tanjungpinang City Regional Regulation Number 7 of 2010 concerning Building. The objectives of the study is to evaluate whether the buildings in Tanjungpinang City have met the requirements and they are in accordance with the functions and spatial planning. It also analizes the legal certainty in the implementation of the building permit in this city.